Analisis Pengaruh Product Quality dan Service Quality Terhadap Loyalitas Konsumen Pada Warkop Rifqi Jaya Tuasan Medan Tembung - Rahmadi Idris Pasaribu; Sabda Dian Nurani Siahaan (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the influence of Product Quality and Service Quality on Consumer Loyalty at Warkop Rifqi Jaya Tuasan, Medan Tembung. The method used is quantitative research with a purposive sampling technique. The population in this study consists of Warkop Rifqi Jaya Tuasan consumers who have visited more than four times in one month. Data processing was carried out with the help of SPSS software version 26. The results of the study indicate that Product Quality has a positive and significant influence on Consumer Loyalty, as well as Service Quality which also has a positive and significant influence on Consumer Loyalty. Simultaneously, both variables Product Quality and Service Quality have a positive and significant influence on Consumer Loyalty.